Patient-Reported Outcome for Endovascular Treatment versus Microsurgical Clipping in Aneurysmal Subarachnoid Hemorrhage - Arshad Ali (638656) (2021)
Objective Aneurysmal subarachnoid hemorrhage has a high mortality with significant impact on quality of life despite effective management strategies including endovascular treatment and/or microsurgical clipping. Although the modalities have undergone clinical comparison, they have not been evaluated on patient-reported outcomes (PROs). This study compared endovascular versus microsurgical treatment using a PRO measure. Methods We conducted a cross-sectional telephonic survey of adult patients conducted at Hamad General Hospital, Doha, Qatar between 2017 and 2019. Candidate study participants were identified from procedure logs and hospital electronic health records for endovascular treatment (N = 32) versus microsurgical clipping (N = 32) of cerebral aneurysm. The primary outcome measure was the short version of the Stroke-Specific Quality of Life (SS-QoL) measure. The secondary outcome measure was the screened clinician-reported modified Rankin Scale (mRS) for all screened patients (n = 137). Mean scores were compared for the 2 treatment groups. Results The SS-QoL mean score was 4.23 (standard deviation ± 0.77) in endovascular treatment and 4.19 ± 0.19 in surgical clipping (P = 0.90). In exploratory analysis, mean physical domain score was 3.17 ± 0.60 versus 2.98 ± 0.66 in endovascular treatment and surgical clipping groups, respectively. Mean psychosocial domain scores were 4.43 ± 0.85 versus 4.18 ± 0.0.92, respectively. In multivariable analysis, none of the clinical variables were significantly related to SS-QoL except vasospasm irrespective of intervention received. In secondary outcome analysis, modified Rankin Scale score was higher for endovascular treatment (P = 0.04). Conclusions Published evidence has supported clinical benefits of endovascular treatment for cerebral aneurysm treatment, but this study did not find any difference in PROs. Future studies of treatments should include PRO to identify potential differences from the patient's perspective. Other Information Published in: World Neurosurgery License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.wneu.2021.08.131